A clinical pilot study of salivary gland secretion for xerostomia patients with Sjögren's syndrome using SPECT/CT. (20th July 2021) - Minami, Yoshiyuki; Ogura, Ichiro
Abstract: Introduction: This study examined whether time‐activity curves (TAC) can be used to differentiate between patients with and without Sjögren's syndrome using SPECT/CT. Methods: Thirteen xerostomia patients (5 with Sjögren's syndrome and 8 without Sjögren's syndrome) underwent SPECT/CT. Salivary gland secretion data were digitally observed, producing separate time‐activity curves (TAC) for the submandibular glands and parotid glands using SPECT/CT. The salivary gland secretion fraction was defined as A (before stimulation test [counts/frame]) divided by B (after stimulation test [counts/frame]). The A/B ratios of patients with Sjögren's syndrome and those without Sjögren's syndrome were compared using the Mann‐Whitney U test for nonparametric data. Results: The A/B ratio of parotid glands with Sjögren's syndrome (1.3 ± 0.2) was significantly lower than for those without Sjögren's syndrome (2.7 ± 0.7). The A/B ratio of submandibular glands with Sjögren's syndrome (1.3 ± 0.4) is significantly lower than for those without Sjögren's syndrome (1.8 ± 0.6). Conclusion: The TAC for the submandibular glands and parotid glands using SPECT/CT may be useful for the objective and quantitative diagnosis of Sjögren's syndrome.